2003
DOI: 10.1097/00001888-200305000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Medical Studentsʼ Training in End-of-life Communication

Abstract: These interns, mostly U.S. medical school graduates (98.7%, n = 155) reported little training and low self-perceived comfort and skill with important elements of end-of-life communication that might contribute to a lack of preparedness to address these issues during their internship. Further research that confirms and explains the underlying reasons for these findings seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 27 publications
1
53
0
1
Order By: Relevance
“…25 Reflecting this lack of training, medical students and residents feel unprepared to take care of dying patients. 26 In one survey, hospitalists reported that although palliative care was very important to their practice, they had not received enough training in palliative care knowledge and skills. 27 …”
Section: Fear Of Taking Away Hopementioning
confidence: 99%
“…25 Reflecting this lack of training, medical students and residents feel unprepared to take care of dying patients. 26 In one survey, hospitalists reported that although palliative care was very important to their practice, they had not received enough training in palliative care knowledge and skills. 27 …”
Section: Fear Of Taking Away Hopementioning
confidence: 99%
“…8,9 However, most medical students have inadequate palliative care knowledge 3 and do not receive appropriate end-of-life education. 10,11 To date, only half of Taiwan's medical schools have compulsory palliative medicine training in their undergraduate program. 12 Unlike Taiwan, end-of-life medical education has sharply increased in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Even if it is something you've never experienced, you can open up your mind and heart to what other people are going through" (Gravett, 2011). Comics' potential to facilitate empathy and understanding may be particularly relevant for teaching about ethics and end-of-life (EOL) care, as recent studies have shown that medical students and interns are not adequately prepared to address EOL issues with patients (Buss et al, 1998; Ury et al, 2003;Siu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%